Catalytic Hydrogenolysis of Substituted Diaryl Ethers by Using Ruthenium Nanoparticles on an Acidic Supported Ionic Liquid Phase (Ru@SILP-SO3H) - Rengshausen, Simon; Etscheidt, Fabian; Großkurth, Johannes; Luska, Kylie L.; Bordet, Alexis; Leitner, Walter (Synlett, 2019)
Catalytic hydrogenolysis of diaryl ethers is achieved by using ruthenium nanoparticles immobilized on an acidic supported ionic liquid phase (Ru@SILP-SO3H) as a multifunctional catalyst. The catalyst components are assembled through a molecular approach ensuring synergistic action of the metal and acid functions. The resulting catalyst is highly active for the hydrogenolysis of various diaryl ethers. For symmetric substrates such as diphenyl ether, hydrogenolysis is followed by full hydrodeoxygenation producing the corresponding cycloalkanes as the main products. For unsymmetric substrates, the cleavage of the C–O bond is regioselective and occurs adjacent to the unsubstituted phenyl ring. As hydrogenation of benzene is faster than hydrodeoxygenation over the Ru@SILP-SO3H catalyst, controlled mixtures of cyclohexane and substituted phenols are accessible with good selectivity. Application of Ru@SILP-SO3H catalyst in continuous-flow hydrogenolysis of 2-methoxy-4-methylphenoxybenzene is demonstrated with use of commercial equipment.
Keywords: ruthenium nanoparticles; acidic SILP; multifunctional catalysis; diaryl ether cleavage; hydrogenolysis; deoxygenation; lignin